Use Of Educational Technologies In Teaching The Subject "Static Exact Steel Structures And Their Calculation Methods" (Eurasian Journal of Learning and Academic Teaching, 2022)
This article describes the methods of using innovative educational technologies in the teaching of static concrete steel structures and their calculation methods